High proportions of post-exertional malaise and orthostatic intolerance in people living with post-COVID-19 condition: the PRIME post-COVID study - Pagen, Demi M. E.; Van Herck, Maarten; van Bilsen, Céline J. A.; Brinkhues, Stephanie; Konings, Kevin; den Heijer, Casper D. J.; Spruit, Martijn A.; Hoebe, Christian J. P. A.; Dukers-Muijrers, Nicole H. T. M. (Frontiers in Medicine, 2023)
Background Exercise-based treatments can worsen/exacerbate symptoms in people who were SARS-CoV-2 positive and living with post-COVID-19 condition (PL-PCC) and who have post-exertional malaise (PEM) or orthostatic intolerance (OI). Nevertheless, PEM and OI are not routinely assessed by clinicians. We estimated PEM and OI proportions in PL-PCC, as well as in people not living with PCC (PnL-PCC) and negatives (i.e., never reported a SARS-CoV-2 positive test), and identified associated factors. Methods Participants from the Prevalence, Risk factors, and Impact Evaluation (PRIME) post-COVID-19 condition study were included. PEM and OI were assessed using validated questionnaires. PCC was defined as feeling unrecovered after SARS-CoV-2 infection. Multivariable regression analyses to study PEM and OI were stratified for sex. Results Data from 3,783 participants were analyzed. In PL-PCC, the proportion of PEM was 48.1% and 41.2%, and the proportion of OI was 29.3% and 27.9% in women and men, respectively. Proportions were higher in PL-PCC than negatives, for PEM in women OR=4.38 [95%CI:3.01–6.38]; in men OR = 4.78 [95%CI:3.13–7.29]; for OI in women 3.06 [95%CI:1.97-4.76]; in men 2.71 [95%CI:1.75–4.21]. Associated factors were age ≤ 60 years, ≥1 comorbidities, and living alone. Conclusion High proportions of PEM and OI are observed in PL-PCC. Standard screening for PEM and OI is recommended in PL-PCC to promote appropriate therapies.